Uji Kuat Tekan Bata Beton Dengan Bahan Ikat Kapur dan Abu Terbang - Rezkhy Akbar; Hamka; Jabir, Muhammad (Jurnal Karajata Engineering, 2024)
Limestone is one of many potentials in Indonesia, especially Suppa Kab. Battery Rating. The use of lime minimizes the use of cement mixed with fly ash. Fly ash in PLTU, especially in Kab. Barru uses coal as fuel and turns its waste into fly ash. The aim of this study was to determine the efficiency of using fly ash and lime as binder in concrete brick mix and to determine the variation of the mixture to give maximum concrete strength. This research method uses experimental method carried out at Muhammadiyah Parepare University's Laboratory of Structural and Materials in March-May, 2023. The results show that the compressive strength test on ordinary concrete is carried out. is 3.26 MPa, AT70%:KA30% of 2.69 MPa, AT80%: KA20% of 2.83MPa, AT90%:KA10% of 4.10MPa. From that, it can be concluded that concrete bricks have AT90% variation. The KA10% reaches the design compressive strength and is suitable for use, while the AT70% variant KA30% does not achieve the designed compressive strength and is not suitable for use.